Integrin–protein kinase C relationships. (1st February 2003) - Ivaska, J.; Kermorgant, S.; Whelan, R.; Parsons, M.; Ng, T.; Parker, P.J.
Abstract : The integrins have an ability to interact with extracellular matrix proteins to confer adhesive and motile properties on cells. The means by which these activities operate and the manner in which they are integrated with cell functions is of particular relevance to many biological processes. In the present paper, the developing understanding of the bi-directional relationship between the protein kinase C family of signal transducers and integrins is discussed.